A multicentric real-world observational study to describe the use and efficacy of follitropin delta for IVF/ICSI procedures in patients at risk of hypo-response - Deloire, Anne-Claire; Porcu-Buisson, Géraldine; Lefebvre, Romane; Bernot, Mathilde (Frontiers in Reproductive Health, 2025)
BackgroundAround 20% of patients undergoing assisted reproductive technology are at risk of hypo-response to ovarian stimulation. The aim of this study was to describe the real-world use of follitropin delta for ovarian stimulation in these patients, as defined by POSEIDON groups 3 and 4 [an anti-Müllerian hormone (AMH) level of <1.2 ng/ml].Materials and methodsThis study was a post-hoc analysis of participants from DELTA, a multi-centre, prospective, observational study conducted in normal care settings in fertility clinics at 14 active sites in France. A subset of 35 patients at risk of hypo-response to ovarian stimulation (mean AMH 0.7 ± 0.29 ng/ml) and treated with follitropin delta were included. Patients were followed for 10–11 weeks after the first fresh or frozen embryo transfer in case of subsequent pregnancy, and data on real-world follitropin delta use collected.ResultsMost patients (92.9%) had undergone their first IVF or ICSI. The prescribed daily dose was usually based on the approved algorithm (N = 26; 74.3%) with a mean daily dose of 14.2 ± 4.1 mcg, resulting in a mean total dose of 187.7 ± 135.6 mcg. The mean duration of ovarian stimulation was 11.6 ± 6.7 days with no premature discontinuations, while the mean number of oocytes retrieved among patients that started stimulation was 6.3 ± 4.3. A fresh transfer was performed for 21 patients (84.0%), with a mean of 1.04 ± 0.98 embryos transferred per patient. Seven patients (20.0%) achieved an ongoing pregnancy (28% per transfer). No adverse drug reactions were reported.ConclusionsThe results describe the real-world use of follitropin delta and demonstrate its suitability for POSEIDON group 3 and 4 patients. These data complement clinical trial outcomes, supporting clinician decision-making and improving IVF/ICSI outcomes.